The effect of tocotrienol-rich fraction on oxidative liver damage induced by fenitrothion - Putri Ayu Jayusman,; Siti Balkis Budin,; Izatus Shima Taib,; Ahmad Rohi Ghazali, (Penerbit Universiti Kebangsaan Malaysia, 2017)
Exposure to organophosphate pesticide including fenitrothion (FNT) has led to many adverse effects on human health. However, a potent antioxidant like palm oil tocotrienol-rich fraction (TRF) can reduce oxidative damage in various pathological conditions, could also reduce the adverse effects by FNT. The aim of this study was to evaluate the effect of TRF on oxidative liver damage in FNT induce hepatotoxicity in experimental rats. A total of 40 male Sprague-Dawley rats were randomly divided into four groups of 10, namely control, TRF, FNT and TRF+FNT group. TRF (200 mg/kg body weight) and FNT (20 m/kg body weight) were administered through oral gavage for 28 days. Corn oil which served as vehicle was given orally to the control group. At the end of the study period, liver and blood was taken for oxidative damage and biochemical evaluation and histological observation. TRF supplementation prevents oxidative liver damage by reducing the hepatic malondialdehyde (MDA) and protein carbonyl (PCO) level significantly. Besides, TRF also restored the endogenous antioxidants particularly reduced glutathione (GSH), glutathione peroxidase (GPx) and ferric reducing/antioxidant power (FRAP). TRF also prevent liver damage by reducing the liver enzymes, alanine aminotransferase (ALT) and aspartate aminotransferase (AST). The attenuation of liver damage by TRF was also showed histologically. In conclusion, TRF supplementation showed a potential in preventing oxidative liver damage in FNT-treated rats by reducing the oxidative damage and improving the antioxidant status.